Antifragile approach for ice-hockey team performance modeling: the definitions component - Géczi, G. (2021)
Antifragile operation of a system depends on the structure it is built upon. The paper presents definitions upon which a model of ice-hockey team performance lies, thus providing the robustness to the system, next to a human factor responsible for getting the needed stimuli to evolve towards antifragile operation. The author collected six definitions for each of the factors of the model, and created his own definitions providing the supporting pillars of the evolving system. It is concluded that the robustness of the system, backed up by the definitions component, is expected to give birth to an emergent state in which the balance between team cohesion and openness is found by the team as a whole supporting antifragile operation.